2020
DOI: 10.1002/mnfr.201900905
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Piceatannol, a Dietary Resveratrol Derivative: Promises to Human Health

Abstract: Scope: To evaluate the health-promoting potentials of piceatannol (PIC), a dietary resveratrol derivative, its biotransformation is examined. Methods and results: The biotransformation is tested in human/rat hepatic microsomes and cytosols; its pharmacokinetic profiles are assessed in rats. Although limited phase I metabolism exists in microsomes, PIC is rapidly converted to two pharmacologically active metabolites, namely rhapontigenin (RHA) and isorhapontigenin (ISO) in cytosols. Such biotransformation is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Therefore, Pic had a higher absorption and a higher metabolic stability than Res [ 28 ]. Moreover, a recent study reported that Pic converted to isorhapontigenin (Iso) in rats after oral administration [ 41 ]. Iso possesses a higher oral bioavailability and anti-inflammatory effects in chronic obstructive pulmonary disease than Res [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Pic had a higher absorption and a higher metabolic stability than Res [ 28 ]. Moreover, a recent study reported that Pic converted to isorhapontigenin (Iso) in rats after oral administration [ 41 ]. Iso possesses a higher oral bioavailability and anti-inflammatory effects in chronic obstructive pulmonary disease than Res [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it should be highlighted that stilbenes such as piceatannol glucoside (< LOQ), piceatannol (0.17 mg/100 g of fruit) and trans-resveratrol (0.06 mg/100 g of fruit) were only detected in passion fruits. Piceatannol similar to its precursor resveratrol showed health-promoting properties such as antiaging, anticarcinogenic, anti-diabetic, anti-inflammatory, antiobesity properties, as well as cardio-, hepato-and neuro-protection, in several pre-clinical studies (Dai et al, 2020;Kershaw and Kim, 2017;Wen et al, 2018;Zhang et al, 2018).…”
Section: Methods Validation and Semi-quantification Of Phenolic Compounds In Tropical Fruitsmentioning
confidence: 99%
“…After drying, the DBS were punched, and the cores (6 mm) obtained were placed inside the respective Eppendorf tubes. All the acquired DBS were stored at −80 • C until processing for analysis [27,28]. One DBS was used for metabolomic analysis and the other one was used for drug level quantification.…”
Section: Animalsmentioning
confidence: 99%